2020
DOI: 10.5620/eaht.2020023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfur dioxide, ozone, and ambient air pollution on bone metabolism related biochemical parameters in a rat model

Abstract: Ambient air pollution (AAP), as an important environmental health problem, affects everyone. A large body of literature links AAP, such as sulfur dioxide (SO2) and ozone (O3), with a wide range of non-communicable diseases. The aim of the present study was to investigate the effects of the pollutants on the bone metabolism biochemical parameters in a rat model. Thirty-two male Wistar rats were divided to four groups: control, SO2 (10 ppm), O3 (0.6 ppm), and AAP groups. After 5 weeks of exposure (3 hours/day, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…10 Our ndings have also been now con rmed in multiple human studies [11][12][13][14][15][16] and are supported by animal studies. 17 We have also con rmed the effect of exposure to several air pollutants on reduced BMD and fractures in postmenopausal women. 18 Recent human studies show that even low concentrations of ambient air pollution can affect the levels of several metabolites 19,20 that affect bone-related metabolites such as αtocopherol 21,22 and glycine.…”
Section: Introductionmentioning
confidence: 58%
“…10 Our ndings have also been now con rmed in multiple human studies [11][12][13][14][15][16] and are supported by animal studies. 17 We have also con rmed the effect of exposure to several air pollutants on reduced BMD and fractures in postmenopausal women. 18 Recent human studies show that even low concentrations of ambient air pollution can affect the levels of several metabolites 19,20 that affect bone-related metabolites such as αtocopherol 21,22 and glycine.…”
Section: Introductionmentioning
confidence: 58%
“…yielded no noteworthy differentiation in β-CTX levels between adolescents inhabiting polluted and unpolluted locales ( 54 ). A basic study found that rats exposed to air pollutants had significantly higher ALP levels than the control group ( 55 ). There was limited research on the correlation between air pollution and PINP, which made it challenging to compare our current findings with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental toxins such as dioxins, bisphenols, polychlorobiphenyls, phthalates, poly- and perfluoroalkyl, parabens, particulate matter (PM), and heavy metals can impact bone health by interfering with bone homeostasis through a variety of processes [ 98 , 99 , 100 , 101 , 102 ]. These include hormonal imbalance, direct osteoblast toxicity, and enhancement of osteoclast activity, leading to different bone-related ailments.…”
Section: Intrinsic and Extrinsic Variables Affecting Bone Healthmentioning
confidence: 99%